Intelligent Environmental Recognition Features of “Robosofa” - Maskeliunas, R.; Raudonis, V.; Bukis, A. (Elektronika ir Elektrotechnika, 2012)
The detailed review of state of the art techniques and algorithms is presented in this work, aiming to create the autonomous mobile platform for mobility improvement of disabled persons. The video camera, sixth infrared range sensors and the motorized furniture were used in our mobile system. Presented system automatically localizes the position of the “smart” furniture based on certain color markers. The mobile platform is a part of a bigger associative system which is being developed during the project ROBOSOFA. Therefore, the main focus of this paper is on the self localization problem from visual information, i.e., the images of colored markers. The recognition task of the certain room is limited by the signals from range sensors and the recognition of the certain markers, because each room is coded with different color markers. Intermediate experimental results show, that the proposed algorithm can be applied in real time applications and it is able to process 20 frames per second. Ill. 6, bibl. 20 (in English; abstracts in English and Lithuanian). DOI: http://dx.doi.org/10.5755/j01.eee.117.1.1045